Combination Actuator of the Linear Coordinate System of Technological Equipment with Control Propulsive Force - V.L. Basinyuk (National Academy of Sciences of Belarus, State Scientific Institution “The Joint Institute of Mechanical Engineering", 2013)
The problems of constructing of linear drives with traditional toothed belt transmissions for coordinate systems of technological equipment, used for cutting semiconductor wafers with diamond wheel are discussed. The possibilities of a significant improvement in their dynamic qualities by creating a combination actuator wherein in addition to the main motor in the construction is entered another relatively low-powered program-controlled linear electromotor are shown. Its armature is directly connected with the movable table. With help of the linear electromotor additional program-controlled propulsive force is created under its acceleration or braking the table, it eliminates the occurrence of natural vibrations when it reaches cutting feed rate or stop.